Synthesis of Novel Pyrrolo[3,2-c]carbazole and Dipyrrolo[3,2-c: 2?,3?-g]carbazole Derivatives - Sengul, Ibrahim Fazil; Astarci, Erhan; Kandemir, Hakan (Georg Thieme Verlag Kg, 2016)
Pyrrolocarbazole and dipyrrolocarbazoles have been synthesized via the Hemetsberger indole synthesis, starting from 9-ethyl carbazole-3-carbaldehyde and 9-ethylcarbazole-3,6-dicarbaldeyde, respectively. The pyrrolocarbazole structures were confirmed through H-1 NMR, C-13 NMR, IR, mass spectrometry and single crystal X-ray diffraction techniques. The targeted compounds showed potent in vitro cytotoxicity against human colon cancer HT29 cells.
Keywords: carbazole; pyrrolocarbazole; Hemetsberger indolization; HT29 cells; cyctotoxicity